10.1111/acn.v9999.9999 (CrossRef Listing of Deleted DOIs, 2000)
Background Adrenal crisis is a life-threatening emergency. Despite preventive strategies, previous reports suggest increasing incidence and substantial mortality, but robust validated data are limited. Objective To assess temporal trends in adrenal crisis incidence and identify associated risk factors. Methods We studied 1040 patients with autoimmune or idiopathic primary adrenal insufficiency enrolled in the Norwegian Addison Registry. Medical records were reviewed for crisis-related hospitalizations between 2000 and 2023. Overt adrenal crisis was defined by acute clinical deterioration with hemodynamic or biochemical abnormalities, whereas incipient crisis was defined by typical symptoms without objective abnormalities. Results During a median follow-up of 15 years, 660 patients (63%) experienced crisis-related hospitalizations, and 265 (25%) had an overt adrenal crisis after diagnosis. The incidence of overt crises was 3.2 per 100 person-years and that of incipient crises was 6.9 per 100 person-years. Admission rates for incipient crises increased significantly over time (p < 0.001), whereas overt crisis rates remained stable. Among 1754 admissions, five deaths (0.3%) were attributed to adrenal crisis. Both younger and older age (p < 0.001) and type 1 diabetes (incidence rate ratio 2.09, 95% confidence interval 1.45-3.01; p < 0.001) were associated with increased overt crisis risk. Daily corticosteroid dose was not associated with crisis risk. Prehospital stress dosing was used in about 50% of admissions. Conclusions Overt adrenal crisis was uncommon and crisis-related in-hospital mortality was exceptionally low. Crisis risk was independent of replacement dose but increased in patients with type 1 diabetes. Strengthening education and implementation of prehospital stress dosing may further reduce the burden of adrenal crises.